Effect of job satisfaction on job performance, with quality of work life as moderating among Jordanian hotels: a pilot study - Fazida, Karim; Mahadzirah, Mohamad; Bandar Ersan, Alown (2020)
Employees in the hotel industry are the key personnel who contribute to giving guests the satisfactory experience they expect. Therefore, it is important that every employee strives to improve his/her job. The purpose of this study is to examine the influence of job satisfaction, leadership style, and organisational structure on job performance, with the moderating role of quality of work-life among employees working in Jordanian hotels. The study explores the perceptions of employees working in five-star hotels in Jordan in order to verify the validity and reliability of the study instrument. The study was applied to a small sample, and SPSS analysis software was used. The study validated the reliability of the instrument in conducting a preliminary study, obtaining reasonable normality and highly reliable coefficients of measures (0.927- 0.986). The study validated the effectiveness of the instrument that examined different specific antecedents of job performance.